INTEREST RATE RISK AND THE FINANCIAL PERFORMANCE OF LISTED COMMERCIAL BANKS IN KENYA - Mutinda Prisca Nthenya; Gordon Opuodho; Linus Isaac Ochieng (ZILLZELL MEDIA PRIMA, 2026)
This study examined the impact of interest rate risk on the financial performance of listed commercial banks in Kenya from 2013 to 2023. Using the Interest Rate Parity Theory, it employed a longitudinal approach and conducted a census of all 11 banks listed on the Nairobi Securities Exchange (NSE). These banks are subject to strict oversight by both the Capital Markets Authority (CMA) and the NSE, which require consistent disclosures, financial reporting, audits, and adherence to corporate governance standards. This regulatory environment fosters transparency in asset-liability management (ALM) and risk control, making these banks ideal for studying the relationship between interest rate risk and financial performance. The research utilized secondary data from annual financial statements and reports from the Central Bank of Kenya. Financial performance was measured using Return on Assets (ROA). Panel regression analysis revealed a positive association between interest rate risk management and financial performance, indicating that banks with stronger interest rate risk management tend to perform better. The findings suggest that Kenyan-listed banks have maintained consistent and effective interest rate risk management over the decade, thereby contributing to their stability amid economic uncertainty. Enhanced interest rate management further improved their resilience and financial outcomes. The study recommends that banks maintain robust hedging strategies, conduct regular interest rate stress tests, and perform scenario analyses to guard against unexpected interest rate fluctuations and promote sustainable growth.